(untitled) (Journal of Open Law, Technology & Society, 2019)
With the increasing use of Free and Open Source Software (FOSS) in the world, the licensing issues and disputes regarding such licenses have been litigated in various jurisdictions. In the past, these lawsuits were concentrated in Europe and the United States, but less so in the Asia Pacific region. However, in 2018, the specialized Intellectual Property Right Court in Beijing, China, acting as a court of first instance, issued a decision in a software copyright infringement lawsuit related to FOSS. The defendant chose to invoke the copyleft mechanism in the GNU General Public License 3.0 (GPL-3.0) license as a defense against claims of copyright infringement. Although the court did not directly interpret the GPL license at this stage, the decision strongly implies that the GPL and the other FOSS licenses can be treated as valid in China. Even so, quite a number of details regarding the use of the GPL in China still require clarification, included as to how the license can substantially be enforced and implemented.